A contribuição da leitura do gênero romance na formação do leitor literário no Ensino Fundamental II - Janaína Mendes Silva Ferreira (2020)
A work with Reading in classroom, if properly done through teacher's mediation, can bring a significant experience of literary literacy to student's education like a reader.The proposal of this project was to develop a basic sequence of literary literacy, verifying the contribution of a novel reading in the literary reader’s education in the Junior High School. The research is a qualitative one and was done with students of 8th grade of Junior High School of a public school in the municipality of Pitangui/MG. Rethinking the practice in classroom for literary texts approach, this research wanted to answer the question: What strategies should be used to develop a novel reading in the Junior High School, in order to enable a significant experience of literary literacy that contributes to the literary reader’s education? Bearing this in mind, with the application of the project, the initial hypothesis that through teacher's mediation in the novel reading, using a basic sequence of literary literacy, students can optimize literary readers’ education was confirmed. The datais came collected through questionnaires answered by students, through activities used, through classes observation, through the student’s records in the reader’s diary and through a researcher-teacher's reflexive diary. The practice of this project was based on the Basic sequence of literary literacy proposed by COSSON (2018b). The theoretical reference was based on COSSON (2018a, 2018b, 2011, 2010, 2004), COLOMER (2003, 2017), COSSON; SOUZA (2011), CANDIDO (1989, 1995, 2002), BAKHTIN (2002), SOARES (2006), AGUIAR (2006), ZILBERMAN (2008a, 2008b), CORTÁZAR (2006), MARQUES (2012), TIHANOV (2013). This research is an important opportunity for Portuguese language teachers to rethink how literary reading has been working at school, after all they are mediators in the literary reader’s education.